2015
DOI: 10.1021/acs.est.5b00496
|View full text |Cite
|
Sign up to set email alerts
|

Increased Frequency of Nontuberculous Mycobacteria Detection at Potable Water Taps within the United States

Abstract: Nontuberculous mycobacteria (NTMs) are environmental microorganisms that can cause infections in humans, primarily in the lung and soft tissue. The prevalence of NTM-associated diseases is increasing in the United States. Exposure to NTMs occurs primarily through human interactions with water (especially aerosolized). Potable water from sites across the U.S. was collected to investigate the presence of NTM. Water from 68 taps was sampled 4 times over the course of 2 years. In total, 272 water samples were exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(54 citation statements)
references
References 25 publications
0
54
0
Order By: Relevance
“…Recent outbreak events have been reported in Flint, MI (Legionella) (June, 2014-November, 2015) (MDHHS, 2015), the Bronx, NY (Legionella) (Raphael et al 2016) and Munich, Germany (MAC) (Haller et al 2016). The results from this study and others have shown that the causative microorganisms can be present in water at large and small, newer and older residences (Stout et al 1992;Feazel et al 2009;Donohue et al 2014;Schwake et al 2016) and office buildings (Dutka et al 1984;Flannery et al 2006;Hilborn et al 2006;Moore et al 2006;Donohue et al 2015).…”
Section: Discussionmentioning
confidence: 57%
“…Recent outbreak events have been reported in Flint, MI (Legionella) (June, 2014-November, 2015) (MDHHS, 2015), the Bronx, NY (Legionella) (Raphael et al 2016) and Munich, Germany (MAC) (Haller et al 2016). The results from this study and others have shown that the causative microorganisms can be present in water at large and small, newer and older residences (Stout et al 1992;Feazel et al 2009;Donohue et al 2014;Schwake et al 2016) and office buildings (Dutka et al 1984;Flannery et al 2006;Hilborn et al 2006;Moore et al 2006;Donohue et al 2015).…”
Section: Discussionmentioning
confidence: 57%
“…Most communities use either chlorine or chloramines and switch back and forth between these products at different times of the year or for operational reasons [29]; there is evidence that bacterial communities shift during water disinfection, and mycobacteria have been found to increase during monochloramine treatment [30]. Furthermore, Donohue et al showed that there are statistically significant higher levels of NTM in nonchlorinated than in chlorinated tap water [31]. Unlike the M. abscessus complex outbreak linked to hospital tap water at a tertiary care hospital in Durham, North Carolina [32], the characteristics of the identified cases included in our study failed to fulfill the criteria for an outbreak as the number of reported cases yearly has remained almost the same throughout the 4 years of our study at all the sites of infection; our cases were not clustered in a particular area or hospital unit, nor were they related to a specific procedure or patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Hypersensitivity pneumonitis has been traced to the presence of NTM in shower heads [69]. In the USA, higher concentrations of NTM have been reported in DWDS disinfected with monochloramine than in DWDS disinfected by chlorination [70]. Haig and colleagues used a high-throughput approach to determine that greater water age, i.e., combined DWDS residence time and home plumbing stagnation time, is associated with a greater relative abundance of M. avium, and DW from locations closer to WTPs contain more diverse NTM spp.…”
Section: Plos Onementioning
confidence: 99%